Implementasi Gamifikasi dalam Sektor Publik: Tinjauan Sistematis Berdasarkan Kerangka SPICE - Hartanto, Krisnawan (MAN 4 Kota Pekanbaru, 2026)
Bureaucratic reform in Indonesia is frequently hindered by procedural rigidity and information asymmetry. This study evaluates the effectiveness of gamification as an intervention strategy to address these challenges. Using a Systematic Literature Review based on the SPICE framework, this research analyzes selected literature from the last decade. The results identify two impact clusters: externally, gamification simplifies abstract regulations into interactive simulations, effectively reducing information asymmetry for citizens. However, there are several factors that influence the effectiveness of gamification, some of which are digital literacy and age. Internally, it enhances Civil Servants' engagement in technical training and mitigates rigid work cultures. The study concludes that gamification serves as a strategic policy instrument rather than mere entertainment. It simplifies bureaucratic complexity and bridges public communication through an adaptive psychological approach. These findings imply that integrating game elements into public services significantly improves voluntary compliance and organizational agility, offering a viable solution for modernizing public administration.